This misery of light ‐ light as destruction in the work of Lina Selander. (1st April 2019) - Larsson, Erika
AbstractIn this article I look at two works by Swedish video artist Lina Selander and explore how underlying visual patterns unfold in these works that are connected to certain worldly phenomena. Borrowing from Jacques Derrida, I describe the tendency of being en mal d'archive as an obsession to structure the world into particular recognizable patterns. I argue that Selander's works can be understood as the unfolding of such structures, the result being that the very impulse itself, the obsession Derrida speaks of, comes to the forefront. In several of Selander's works, light is explored both as a basis and prerequisite for photography and as a metaphor for this potentially destructive desire for all-encompassing knowledge and structure. As such, I argue, the unfolding that takes place in her works can be understood as paradoxically increasing the shadows ‐ as a way of undoing the totalizing effect of light and articulating modes of not knowing or mystery in relation to the phenomena explored.